Value-chain analysis — An assessment methodology to estimate Egyptian aquaculture sector performance - MacFadyen, G.; Nasr-Allah, A.M.; Al-Kenawy, D.A.R.; Mohamed, F.; Hebicha, H.; Diab, A.; Hussein, S.; Abou-Zeid, R.M.; El-Naggar, G.O. (2012)
Egypt's aquaculture production (705,490 tonnes in 2009) is by far the largest of any African country and places it 11th in terms of global aquaculture production. The aquaculture sector in Egypt is now a mature one having developed over a period of more than 30 years, but the financial performance of the sector is not well understood or documented, even though value-chain analysis provides a methodological tool to do so. To provide a better understanding of the sector, a WorldFish Center study completed in September 2011 and funded by the Swiss Agency for Development and Cooperation, conducted a value-chain analysis of the pond fish farming sector. The sector concentrates on the production of tilapia with additional production of mullet, catfish and carp from earthen ponds. The study mapped the value-chain and showed that there is no processing and virtually no export of farmed fish, a short time-period from harvest to final consumption by the consumer (typically around one day) due to the live/fresh nature of all sales, and very low rates (< 1%) of post-harvest losses. Quantitative data were collected for each link in the value-chain on operational and financial performance (e.g. gross output values, variable and fixed costs, operational and net profit margins, value-added generation), and on employment creation (by gender, age and full-time/part-time). The results showed that the industry generates a combined LE 4619 ($775) of value-added (i.e. profits plus wages/earnings) for farmers, traders and retailers for each tonne of fish produced. Employment generation is also significant with around 14 full-time equivalent jobs generated for every 100 tonnes of fish produced. However, the sector as a whole is under increasing financial pressure. Critical factors impacting on the performance of the value-chain relate to inputs (most importantly to rising feed costs and the poor quality of fry), to production (most importantly to poor practices with regard to feed management, farm design and construction, fish health management, and stocking densities), and to the marketing, transportation and sale of product (most importantly to declining fish prices in real terms, consumer preference for wild fish and a distrust of filleted/processed products, fluctuating seasonal prices, poor hygiene and handling practices, the lack of value-addition through processing, and the lack of exports). This paper highlights the benefits of value-chain analysis as a useful tool to understand sector performance and argues for its wider use in identifying critical factors and actions to support aquaculture sector improvements.